2022
DOI: 10.1002/nha3.20321
|View full text |Cite
|
Sign up to set email alerts
|

Using a strengths‐based approach to improve employment opportunities for individuals with autism spectrum disorder

Abstract: An increasing number of individuals with autism spectrum disorder (ASD) are pursing postsecondary degrees; however, the employment rate for this population is unacceptably low because of the range of deficit in behavioral, communication, and social skills that are crucial for effective functioning on the job. Although individuals with ASD have wide and varied talents and giftedness, there continues to be a focus on their impairments rather than their strengths and they are subject to stigma and discrimination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Individuals who have a personal relationship with an autistic person have also been found to have more positive attitudes toward autistic individuals (Gibbons et al, 2015;Nevill & White, 2011), suggesting the importance of personal connection and a well-rounded, firsthand understanding of autism. In addition, a strengths-based approach to autism understanding has been shown to improve relationships (Shochet et al, 2019) and has been indicated to improve employment outcomes for autistic adults (Johnson, 2022). In the study of positive psychology, attention has been paid to the importance of a strengthsbased focus, with more recent literature tying the idea to autism and related conditions (Niemiec et al, 2017).…”
Section: Principle 3: Emphasize Strengths and Similarities To Facilit...mentioning
confidence: 99%
“…Individuals who have a personal relationship with an autistic person have also been found to have more positive attitudes toward autistic individuals (Gibbons et al, 2015;Nevill & White, 2011), suggesting the importance of personal connection and a well-rounded, firsthand understanding of autism. In addition, a strengths-based approach to autism understanding has been shown to improve relationships (Shochet et al, 2019) and has been indicated to improve employment outcomes for autistic adults (Johnson, 2022). In the study of positive psychology, attention has been paid to the importance of a strengthsbased focus, with more recent literature tying the idea to autism and related conditions (Niemiec et al, 2017).…”
Section: Principle 3: Emphasize Strengths and Similarities To Facilit...mentioning
confidence: 99%